Heat stress modulates polymorphonuclear cell response in early pregnancy cows: I. interferon pathway and oxidative stress. - Carolina Dos Santos Amaral; Gabrielle Rebeca Everling Correa; Lady Katerine Serrano Mujica; Mariani Farias Fiorenza; Suzan Gonçalves Rosa; Cristina Wayne Nogueira; Valério Marques Portela; Fábio Vasconcellos Comim; William Schoenau; Natalia Pavlovna Smirnova; Alfredo Quites Antoniazzi (PLoS ONE)
One of the major causes of early pregnancy loss is heat stress. In ruminants, interferon tau (IFNT) is the embryo signal to the mother. Once the interferon signaling pathway is activated, it drives gene expression for interferon-stimulated genes (ISGs) and alters neutrophils responses. The aim of the present study was to evaluate interferon (IFN) pathway, ISGs and gene expression in polymorphonuclear leukocytes (PMN) and oxidative stress in dairy cows under heat stress. Pregnant cows had their estrous cycle synchronized and randomly assigned to a comfort or heat stress group. Blood samples were collected at artificial insemination (AI) and on Days 10, 14 and 18 following AI. Pregnant cows were pregnancy checked by ultrasound on Day 30 and confirmed on Day 60 post-AI. Results are presented as mean ± SEM. The corpus luteum (CL) diameter was not different between groups of pregnant cows; concentration of progesterone of pregnant cows on Day 18 following AI was greater in comfort group compared to heat stressed group. Comfort pregnant cows had higher expression of all analyzed genes from interferon pathway, except for IFNAR1, on both Days 14 and 18. Conversely, heat stressed cows did not show altered expression of IFNT pathway genes and ISGs between Days 10, 14, and 18 after AI. The oxidative stress, determined as malondialdehyde (MDA) levels, was greater in heat stress group on Days 10, 14 and 18, independent of pregnancy status. Heat stress negatively influences expression of ISGs, IFN pathway gene expression in neutrophils, and oxidative stress. Our data suggest that lower conception rates in cows under heat stress are multifactorial, with the association of interferon pathway activation and the unbalanced oxidative stress being main contributing factors.